2015
DOI: 10.1038/srep12169
|View full text |Cite
|
Sign up to set email alerts
|

Performance of genetic risk factors in prediction of trichloroethylene induced hypersensitivity syndrome

Abstract: Trichloroethylene induced hypersensitivity syndrome is dose-independent and potentially life threatening disease, which has become one of the serious occupational health issues and requires intensive treatment. To discover the genetic risk factors and evaluate the performance of risk prediction model for the disease, we conducted genomewide association study and replication study with total of 174 cases and 1761 trichloroethylene-tolerant controls. Fifty seven SNPs that exceeded the threshold for genome-wide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Trichloroethylene (TCE) is an industrial solvent and widespread water pollutant most strongly linked to immunotoxicity and autoimmune disease in experimental rodent models (Blossom & Doss, 2007;Cai et al, 2008;Cooper, Makris, Nietert, & Jinot, 2009;Gilbert, Pumford, & Blossom, 2006;Griffin, Blossom, Jackson, Gilbert, & Pumford, 2000;Griffin, Gilbert, Lamps, & Pumford, 2000). There is also evidence to suggest that TCE promotes immune-mediated inflammatory diseases, hypersensitivity and autoimmunity in humans (Cooper et al, 2009;Dai et al, 2015;EPA, 2011;Huang et al, 2015;Khader, Gaffen, & Kolls, 2009;Parks & De Roos, 2014;Zhao et al, 2016). We and others have shown the effect of continuous developmental exposure to TCE in mice encompassing gestation, lactation, and early life generated CD4 + T-cell alterations and/or early signs of tissue inflammation in both normal and autoimmune-susceptible mouse strains (Blossom, Melnyk, Li, Wessinger, & Cooney, 2017;Gilbert, Woodruff, & Blossom, 2014;Peden-Adams et al, 2006;Peden-Adams et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Trichloroethylene (TCE) is an industrial solvent and widespread water pollutant most strongly linked to immunotoxicity and autoimmune disease in experimental rodent models (Blossom & Doss, 2007;Cai et al, 2008;Cooper, Makris, Nietert, & Jinot, 2009;Gilbert, Pumford, & Blossom, 2006;Griffin, Blossom, Jackson, Gilbert, & Pumford, 2000;Griffin, Gilbert, Lamps, & Pumford, 2000). There is also evidence to suggest that TCE promotes immune-mediated inflammatory diseases, hypersensitivity and autoimmunity in humans (Cooper et al, 2009;Dai et al, 2015;EPA, 2011;Huang et al, 2015;Khader, Gaffen, & Kolls, 2009;Parks & De Roos, 2014;Zhao et al, 2016). We and others have shown the effect of continuous developmental exposure to TCE in mice encompassing gestation, lactation, and early life generated CD4 + T-cell alterations and/or early signs of tissue inflammation in both normal and autoimmune-susceptible mouse strains (Blossom, Melnyk, Li, Wessinger, & Cooney, 2017;Gilbert, Woodruff, & Blossom, 2014;Peden-Adams et al, 2006;Peden-Adams et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In extreme cases, some individuals developed a syndrome with severe skin lesions ranging from erythema to exfoliative dermatitis along with toxic epidermal necrolysis accompanying lymphadenopathy and fever. These diverse symptoms were often accompanied by immune-mediated liver injury often termed non-viral hepatitis ( Dai et al, 2015 ). Although the liver manifestations appeared to be T cell-driven, it is not clear whether the immune response was directed toward self as in AIH.…”
Section: Introductionmentioning
confidence: 99%
“…Previous case-control studies have found several genetic risk factors associated with TIHS, including human leucocyte antigen ( HLA)-B*13:01 ,10 rs2857281 in the intron of major histocompatibility complex class I chain - related gene A ( MICA ),11 rs2523557 located HLA-B and MICA ,11 N-acetyltransferase-2 ,12 and tumour necrosis factor (TNF)-α 13. However, no systematic prospective study has been conducted to evaluate the performance of genetic biomarkers in reducing the incidence of TIHS and improving the efficiency of occupational health surveillance.…”
Section: Introductionmentioning
confidence: 99%